Effectiveness of the Flipped Project-Based Learning Model Based on Moodle LMS to Improve Student Communication and Problem-Solving Skills in Learning Programming - Ruslan Ruslan; Lu'mu Lu'mu; M. Miftach Fakhri; Ansari Saleh Ahmar; Della Fadhilatunisa (MDPI AG, 2024)
The acquisition of programming skills is often complex and poses challenges that impede students' progress and understanding. This study aimed to assess the effectiveness of the flipped project-based learning (FPBL) model, implemented via Moodle LMS, in enhancing students' communication and problem-solving abilities in programming education. The study employed a quasi-experimental design with a control group following a blended learning approach and an experimental group utilizing the FPBL model. Purposive sampling was used. Data collection involved pre- and post-tests assessing communication and problem-solving skills, analyzed through paired and independent sample t-tests to evaluate the significance of the observed improvements. These findings demonstrated significantly positive outcomes in the experimental group. For problem-solving skills, the paired sample t-test showed a mean difference of 16.000, a t-value of 5.852, and a significance level of 0.000. Communication skills analysis revealed a mean difference of 7.400, a t-value of 10.418, and a significance level of 0.000. Independent sample t-tests corroborated these results, indicating notable enhancements in both skills in the experimental group compared to the control group. The FPBL model based on the Moodle LMS markedly improved students' communication and problem-solving skills in programming education. Future research should investigate the long-term retention of these skills and the applicability of the model across different disciplines and educational levels.